Enzymatic Desymmetrization of 19‐nor‐Vitamin D3 A‐Ring Synthon Precursor: Synthesis, Structure Elucidation, and Biological Activity of 1α, 25‐Dihydroxy‐3‐epi‐19‐nor‐vitamin D3 and 1β, 25‐Dihydroxy‐19‐nor‐vitamin D3. Issue 14 (4th June 2018) - González‐García, Tania; Verstuyf, Annemieke; Verlinden, Lieve; Fernández, Susana; Ferrero, Miguel
Abstract: In a search for novel vitamin D derivatives of potential therapeutic value, structurally simple but synthetically challenging A‐ring epimers of the 19‐nor‐ Calcitriol [19‐ nor ‐1α, 25‐(OH)2 ‐D3 ] at C1 and C3 were efficiently synthesized. Both analogues (1‐ epi‐ and 3‐ epi ‐19‐ nor ‐Calcitriol) were obtained through a convergent synthesis starting from cis, cis ‐1, 3, 5‐cyclohexanetriol and the protected 25‐hydroxy Grundmann′s ketone. After Julia‐Kocienski coupling of the corresponding C, D‐ring/side chain sulfone fragment with the A‐ring ketone moiety, both vitamin D analogues were isolated. The critical point was how to determine the structural configuration of both diastereoisomers since similar 1 H NMR spectra were observed. For that, a biocatalytic approach was crucial in the synthesis of orthogonally protected derivatives. NMR spectroscopy allows the unambiguous identification of these compounds and as a result the structural elucidation of the desired vitamin D diastereomeric analogues. Affinity studies demonstrated that these 1, 25‐19‐ nor analogues have a very low affinity for the vitamin D receptor compared with 1α, 25‐dihydroxyvitamin D3 or 1α, 25‐dihydroxy‐19‐ nor ‐vitamin D3 . In addition, these analogues have a lower binding affinity for the human vitamin D binding protein than the natural hormone. In vitro cell culture studies revealed that synthesized analogues were less active than 1α, 25‐dihydroxyvitamin D3 in inhibiting cell proliferation. Abstract :